2019
DOI: 10.1111/vop.12704
|View full text |Cite
|
Sign up to set email alerts
|

Horses with equine recurrent uveitis have an activated CD4+ T‐cell phenotype that can be modulated by mesenchymal stem cells in vitro

Abstract: Equine recurrent uveitis (ERU) is an immune‐mediated disease causing repeated or persistent inflammatory episodes which can lead to blindness. Currently, there is no cure for horses with this disease. Mesenchymal stem cells (MSCs) are effective at reducing immune cell activation in vitro in many species, making them a potential therapeutic option for ERU. The objectives of this study were to define the lymphocyte phenotype of horses with ERU and to determine how MSCs alter T‐cell phenotype in vitro. Whole bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
0
18
0
3
Order By: Relevance
“…But even in this context, our data show significant differences in traveled distance, directness, and velocity of ERU cells, even in the quiescent stage of the disease, pointing to subsisting and continuous presence of autoreactive cells between attacks. Furthermore, the detected migration differences in ERU cells and their association to a Th1 response correlate with the predominant Th1 cell phenotype involved in ERU (Gilger et al, 1999;Saldinger et al, 2019). Data from other models show similar changes in migratory parameters.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…But even in this context, our data show significant differences in traveled distance, directness, and velocity of ERU cells, even in the quiescent stage of the disease, pointing to subsisting and continuous presence of autoreactive cells between attacks. Furthermore, the detected migration differences in ERU cells and their association to a Th1 response correlate with the predominant Th1 cell phenotype involved in ERU (Gilger et al, 1999;Saldinger et al, 2019). Data from other models show similar changes in migratory parameters.…”
Section: Discussionmentioning
confidence: 59%
“…The high responsiveness of PBLs of ERU cases to these substances points to the presence of activated, pro-inflammatory Th1 cells within the migrating cell population of ERU horses. Evidence of Th1 cells driving pathogenesis-associated mechanisms in autoimmune diseases such as ERU have previously been proven in several studies, revealing increased transcription of IFN-γ in the vitreous as well as higher levels of IFN-γ expression in PBLs from ERU horses (Gilger et al, 1999;Saldinger et al, 2019). CRALBP additionally caused a more directed migration of ERU cells (Figure 4).…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies showed that, although percentage of CD3+, CD8+, and CD4+ lymphocytes does not differ between healthy horses and those with ERU, only the disease-driving CD4+ T cells have an activated phenotype in ERU horses ( 39 ). These cells show significantly increased expression levels of IFNγ and decreased expression of IL‐10, indicating Th1 immune response ( 39 ). This supports previous findings of increased levels of IFNγ as well as cytokine Interferon gamma-induced protein 10 (IP-10) in serum of ERU horses ( 40 ).…”
Section: Peripherymentioning
confidence: 99%
“…Equine T cell activation can be markedly reduced by co-incubation with adipose‐derived equine mesenchymal stem cells (MSC) in vitro , resulting in downscaling of CD25 as well as intracellular IFNγ, IL-10, and FoxP3 ( 39 ). This feature of MSC might be useful for the development of new therapeutic approaches in ERU ( 53 ), as suggested by in equine immune-mediated keratitis, where subconjunctival injection of autologous MSCs improved clinical signs of disease ( 54 ).…”
Section: Peripherymentioning
confidence: 99%
“…Immunomodulatory effects of MSC could potentially change the course of equine recurrent uveitis (ERU), as increased expression of IFN-γ by cd4+ T cells from horses with ERU decreased after incubation with ADMSC in vitro. Activation of CD4+-T cells was shown to decrease via contact dependent mechanism and PGE2 signaling (253). In cats, MSC therapy was proposed for the treatment of feline eosinophilic keratitis (FEK), as allogeneic ADMSC implanted subconjunctivally showed promising results seen as an effective decrease in the clinical signs of FEK throughout the study (254).…”
Section: Eye Diseasesmentioning
confidence: 99%